2021
DOI: 10.3847/1538-4365/ac1580
|View full text |Cite
|
Sign up to set email alerts
|

Molecules with ALMA at Planet-forming Scales (MAPS). V. CO Gas Distributions

Abstract: Here we present high-resolution (15-24 au) observations of CO isotopologue lines from the Molecules with ALMA on Planet-forming Scales (MAPS) ALMA Large Program. Our analysis employs observations of the (J = 2-1) and (1-0) lines of 13 CO and C 18 O and the (J = 1-0) line of C 17 O for five protoplanetary disks. We retrieve CO gas density distributions, using three independent methods: (1) a thermochemical modeling framework based on the CO data, the broadband spectral energy distribution, and the millimeter co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
159
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 135 publications
(173 citation statements)
references
References 150 publications
12
159
2
Order By: Relevance
“…The disk parameters are given in Table 1. The stellar input spectrum is also taken from Zhang et al (2021) and is the combination of a stellar atmosphere model (Nextgen; Hauschildt et al 1999) and excess UV (Herczeg et al 2004;Dionatos et al 2019), which is dominated by Lyα emission, consistent with observations (Schindhelm et al 2012). The final stellar spectrum is spectral type K5 (4300 K) with a total luminosity of 1.4 L e and 0.01 L e in UV at wavelengths smaller than 200 nm.…”
Section: Methodsmentioning
confidence: 76%
See 2 more Smart Citations
“…The disk parameters are given in Table 1. The stellar input spectrum is also taken from Zhang et al (2021) and is the combination of a stellar atmosphere model (Nextgen; Hauschildt et al 1999) and excess UV (Herczeg et al 2004;Dionatos et al 2019), which is dominated by Lyα emission, consistent with observations (Schindhelm et al 2012). The final stellar spectrum is spectral type K5 (4300 K) with a total luminosity of 1.4 L e and 0.01 L e in UV at wavelengths smaller than 200 nm.…”
Section: Methodsmentioning
confidence: 76%
“…The physical model is a smooth version of the AS 209 model from Zhang et al (2021). The disk parameters are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such observations have revealed that the chemical inventories in disks are markedly different from those seen in molecular clouds, indicating significant processing in the solids and gas that eventually are incorporated into planets. Notably, the CO abundance observed across protoplanetary disks is consistently found to be a factor of 10-100 lower than the canonical interstellar medium (ISM) value of ∼10 −4 (Favre et al 2013;Schwarz et al 2016;Miotello et al 2017;Zhang et al 2019Zhang et al , 2021. Additionally, the bright emission of hydrocarbons in disks points to significantly elevated gas-phase C/O ratios (>1) compared to the interstellar value (∼0.4; Bergin et al 2016;Cleeves et al 2018;Miotello et al 2019;Bosman et al 2021a).…”
Section: Introductionmentioning
confidence: 98%
“…Okuzumi et al 2016) can contribute to the appearance of a dust ring, while chemical rings and gaps appear when the molecules freeze out beyond the icelines. However, whether the iceline coincides with the dust ring is still a matter of debate (Long et al 2018;Huang et al 2018;van der Marel et al 2019;Zhang et al 2021). On the other hand, there are also mechanisms of dust ring formation, e.g., the Secular Gravitational Instability (Tominaga et al 2020) (Jiang & Ormel 2021), which do not necessarily require that gas and dust substructures correlate spatially.…”
Section: Introductionmentioning
confidence: 99%